SURFACE WATER RESOURCE MANAGEMENT: INTEGRAL PAYMENT FOR ENVIRONMENTAL SERVICES FOR SUSTAINABLE PROSPERITY - Lukito Harjo; Alifone Firdaus Nurwicaksono Adi (Karimun University, 2023)
This study aims to: 1) examine government facilitation in connecting providers and users of surface water resources. 2) examine the form of sustainable welfare improvement in a balanced manner. 3) examine the form of increased profits for providers, users, and the government. This research is longitudinal qualitative research, with secondary data obtained through multiple sites. Regular analytical discussions sharpen thinking through a mix of creativity and systematic search. The findings of this study: a) The government in facilitating the providers and users of surface water resources through legal products and spatial planning policies. b) Increasing sustainable welfare in a balanced manner requires an economic valuation of natural resources as the basis for calculating the value of environmental services, natural resource balance, and green GDP or GRDP. c.) Increasing mutual benefit is the realization of social, environmental, and economic functions that are orderly, harmonious, and avoid disasters, as mandated in Law No. 7 of 2004, Law no. 26 of 2007, and Law no. 32 of 2009. The benefits of providers are in the form of economic improvement, user benefits in the form of sufficient water needs in their business without interruption, and government benefits in the form of reduced conservation costs, conflict resolution costs, disaster emergency costs, and increased taxes. The core of the discussion is the realization of PES for surface water resources in an integral and balanced manner capable of supporting various material and non-material improvements of the three groups.